Evolutionary genetic approach of Carrion's disease. MN, Ss, Diego, Duffy blood groups polymorphisms and clinical stages in endemic areas of Bagua, Amazonas, Peru. - Acosta, Oscar (2011)
phases of Carrion's disease, interpreted in a coevolutive genetic context of amerindian hosts with Bartonella bacilliformis. Design: Associative and analytical study. Setting: Daniel A. Carrion Tropical Medicine Institute, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Bagua Grande, Amazonas, Peru settlers. Interventions: MN, Ss, Duffy and Diego blood groups were determined using standard methodology in 40 Tomocho-Collicate-Vista Hermosa settlers (background of benign or verrucose phase cases without apparent acute phase) and 36 residents of Miraflores area (background of only acute phase cases), Bagua Grande, Amazonas. Main outcomes measures: Phenotypic and allele frequencies of these blood groups in the localities studied. Results: There were no significant differences between the phenotypic, genotypic or alleles frequencies of the MN, Ss, Diego, Duffy blood groups in the Tomocho-Collicate-Vista Hermosa areas (predominance of the verrucose phase) and the Miraflores area (predominance of the acute phase), Bagua Grande, Amazonas. The most variable frequency was found in the MN group, but it was within Hardy-Weinberg equilibrium. Conclusions: Ss, Duffy and Diego blood markers, including the most variable MN, were unrelated to Carrion's disease clinical phases in the localities studied. However, in the context of evolutionary genetic approach, association must be assessed in other endemic areas of the country, as well as susceptibility, resistance and other clinical features of this ancient disease.